(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2024)
The antibacterial effects of Uncaria gambir extract have the potential to be expanded in dentistry, mainly in the management of dental caries and its sequelae. This preliminary study was conducted to investigate the in vitro antibacterial activity of methanolic extract of U. gambir against dental caries-related microflora: Streptococcus mutans, Streptococcus sobrinus, Lactobacillus casei and Enterococcus faecalis. The methanolic extract of U. gambir in powder form was dissolved and serially diluted in 1% dimethyl sulfoxide. The antibacterial effects of the extract were determined using the broth microdilution technique. A transmission electron microscope (TEM) was used to assess the effects of the extract on the morphology of the bacteria. A 0.12% chlorhexidine (CHX) and Man-Rogosa-Sharpe/brain heart infusion broth were used as positive and negative control respectively. Greatest antibacterial effects were seen on both Streptococci species with the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) values of 1.25 and 5 mg/mL respectively, followed by Enterococcus faecalis (MIC=2.5 mg/mL, MBC=10 mg/mL) and Lactobacillus casei (MIC=7.5 mg/mL, MBC=30 mg/mL) in ascending order. Cell wall damage of all bacteria at their respective MIC value was observed through the TEM analysis. Tukey’s posthoc test showed no statistically significant difference in the antibacterial activity exerted by U. gambir extract and 0.12% CHX, with P> 0.05. Conclusively, U. gambir extract exhibits a good antibacterial effect against the microflora of dental caries and carries great potential for future development.